2013
DOI: 10.1089/jwh.2012.4214
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities Among Sexual Minority Women Veterans

Abstract: Background: Lesbian and bisexual (i.e., sexual minority) identity is more common among women veterans than among male veterans. Unique health issues have been identified among women veterans and among sexual minority women, but little is known about women who are both sexual minorities and veterans. This study aimed to compare demographic and health information from sexual minority women veterans with sexual minority women non-veterans and heterosexual women veterans. Methods: Behavioral Risk Factor Surveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 38 publications
2
42
0
1
Order By: Relevance
“…Kavanaugh, 2009). Six studies found no differences in weight by sexual orientation (Blosnich et al, 2013(Blosnich et al, , 2014Bogaert, 2010;Farmer et al, 2013;Hatzenbuehler et al, 2013;Polimeni et al, 2009;Richmond et al, 2012). The remainder found lesbian/bisexual women to be significantly heavier or more likely to be obese with the exception of one study that had no heterosexual comparison group (Fredriksen-Goldsen et al, 2012a).…”
mentioning
confidence: 94%
“…Kavanaugh, 2009). Six studies found no differences in weight by sexual orientation (Blosnich et al, 2013(Blosnich et al, , 2014Bogaert, 2010;Farmer et al, 2013;Hatzenbuehler et al, 2013;Polimeni et al, 2009;Richmond et al, 2012). The remainder found lesbian/bisexual women to be significantly heavier or more likely to be obese with the exception of one study that had no heterosexual comparison group (Fredriksen-Goldsen et al, 2012a).…”
mentioning
confidence: 94%
“…For MSM, sexual minority stress and stigma may influence psychological and behavioral vulnerabilities, including problematic substance use (Boroughs et al, 2015; King et al, 2003) and low self-esteem (Berg et al, 2013; Zervoulis et al, 2015), which may affect high-risk behaviors (Hatzenbuehler, 2009; Meyer, 2003). Studies have identified that sexual minority men and women have greater levels of psychological distress and drug use than their heterosexual peers (Blosnich et al, 2013; King et al, 2003), which could be due to ego depletion (Baumeister et al, 1998) or negative reinforcement pathways (Baker et al, 2004) associated with minority stress. Further, sexual minority individuals also have significantly greater prevalence of mental and physical illnesses, possibly linked to discrimination (Lehavot et al, 2016; Warner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we did not integrate measures of social support and mental health into this analysis; yet, other research suggests this is another area where disparities by sexual orientation may contribute to inequities in physical health outcomes. 3,20 …”
Section: Discussionmentioning
confidence: 99%